Community-Based Social Media Literacy Training For Youth Empowerment In Nagari Rao-Rao - Dasa Syawal Syahputra; Karo, Tiy Kusmarrabbi; Halim Tawakal; Hibatul Haqqi (ASSUNNAH PRESS, 2025)
Social media usage among teenagers has become a serious concern due to the potential negative impacts of inadequate digital literacy. This community service research aims to analyze the effectiveness of community-based social media literacy training in enhancing understanding and skills for responsible social media use among teenagers in Nagari Rao-Rao, Sungai Tarab District, West Pasaman Regency. The methodology employed a participatory action research approach with structured training techniques conducted over six days for 60 MTs Plus Thawalib Darul Huda students. Data were collected through pre-test and post-test assessments, participatory observation, and focus group discussions. Data analysis utilized descriptive statistics and thematic content analysis. The results demonstrated significant improvements in understanding social media concepts (from 45% to 78%), awareness of psychological-social impacts (from 38% to 82%), and hoax identification skills (from 32% to 75%). Community-based training improved digital literacy among rural teenagers by incorporating local values and fostering active community participation. This approach successfully created a holistic learning ecosystem that integrates traditional wisdom with modern digital competencies, providing a culturally responsive model for digital literacy education in Islamic rural communities.